Pengaruh Intervensi Sadar Puasa Ramadan terhadap Asupan Zat Gizi Makro, Serat, Gula dan Aktivitas Fisik diantara Remaja Putri Gizi Lebih: Pengaruh Intervensi Sadar Puasa Ramadan terhadap Asupan Zat Gizi Makro, Serat, Gula dan Aktivitas Fisik diantara Remaja Putri Gizi Lebih - Khairizka Citra palupi; Nurul Shiva Fauziah; Dessy Aryanti Utami; Lintang Purwara Dewanti; Putri Ronitawati (Amerta Nutrition, 2022)
Background: The prevalence of overweight among adolescents 13-18 years from 7.1% to 14.1% between 1993 and 2014, respectively. Mindfulness and Ramadan Fasting have gained attention in treatment of overweight. Objectives: We evaluate the efficacy of Mindful Ramadan Fasting Intervention (MRFI) versus Standard Dietary for Ramadan Fasting (SDRF) in adolescent girls with overweight for improving dietary intake and physical activity Methods: Forty eight overweight adolescents girls from Public Senior High School (age 15 – 17 years) were randomized to MRFI or SDRF groups. The MRFI was administered in six 60-min sessions nutrition education with mindfulness approach and SDDR was provided in six nutrition education brochure administration. Nutrition education was conducted over two weeks before Ramadan Fasting. Two weeks before and after Ramadan Fasting, dietary macronutrients, fiber and sugar intake were measured by 2x24 hour recall , physical activity was measured by IPAQR and  body mass index for age was measured by digital weighing and stadiometer. Results: The proportion of improvement in nutritional status was 29.1 % in MRFI group and 8.3% in SDRF group. Dietary energy and carbohydrates were significantly decreased among both MRFI and SDDR groups (p-value <0.05). Dietary protein and fiber were significantly decreased in MRFI group (p-value <0.05). Dietary fiber was not significantly decreased among both MRFI and SDDR groups (p-value >0.05). Independent t-test showed that there was no difference of dietary macronutrients, fiber and sugar in both MRFI and SDRF groups (p-value > 0.05). Physical activity was significantly decreased among both MRFI and SDRF groups (p-value < 0.05). However, independent t-test showed there was no difference of physical activity among both MRFI and SDDR groups (p-value > 0.05) Conclusions: Both MRFI and SDDR intervention showed feasibility to cure overweight among adolescents girls in urban areas. However, MRFI intervention shows greater improvement in nutrition status and energy intake especially carbohydrates.